Juridical analysis of law enforcement on illegal cigarettes in Batam and its impact on state excise revenue - Muhammad Yadi; Fadlan Fadlan; Parameshwara Parameshwara; Soerya Respationo; Siti Nurkhotijah (Goodwood Publishing, 2025)
Purpose: Analyze law enforcement against illicit cigarettes with counterfeit excise bands in Batam and its impact on excise revenue, framed by Radbruch’s legal certainty, Friedman’s legal system, and Becker’s economics of crime. Research methodology: A normative–empirical legal approach: review of excise laws and implementing regulations; a case study of KPU BC Batam operations (sea/land patrols, risk-based intelligence); semi-structured interviews with officers; and qualitative analysis of enforcement documents. Results: Enforcement produced sizable seizures and a clear typology of illicit excisable goods (without bands/counterfeit), yet constraints persist: limited personnel and assets, a vast surveillance area, and increasingly sophisticated modus operandi. Regulatory gaps channel many cases into administrative settlement (state-asset confiscation) with weak deterrence; inter-agency coordination remains uneven; and permissive social norms toward cheaper prices endure. The main impacts are excise revenue leakage, unfair competition for compliant firms, and erosion of tobacco-control objectives. Conclusions: Legal certainty is not yet achieved due to sanction disparities and inconsistent enforcement; economically, offenders’ expected gains exceed expected penalties. Stronger, predictable, and deterrence-oriented enforcement is required. Limitations: Evidence is confined to Batam and specific periods; there is no econometric estimate of revenue loss; findings rely on interviews and secondary documents. Contribution: Integrates legal theory and policy analysis by proposing tighter norms and recalibrated criminal–administrative sanctions, clarified procedures, deeper inter-agency integration, deployment of digital track-and-trace for excise bands, and public education to curb demand, restore the revenue base, and protect fair competition.